Geospace exploration project ERG - Yoshizumi Miyoshi; Iku Shinohara; Takeshi Takashima; Kazushi Asamura; Nana Higashio; Takefumi Mitani; Satoshi Kasahara; Shoichiro Yokota; Yoichi Kazama; Shiang-Yu Wang; Sunny W. Y. Tam; Paul T. P. Ho; et al. (Earth, Planets and Space, 2018)
Abstract The Exploration of energization and Radiation in Geospace (ERG) project explores the acceleration, transport, and loss of relativistic electrons in the radiation belts and the dynamics for geospace storms. This project consists of three research teams for satellite observation, ground-based network observation, and integrated data analysis/simulation. This synergetic approach is essential for obtaining a comprehensive understanding of the relativistic electron generation/loss processes of the radiation belts as well as geospace storms through cross-energy/cross-regional couplings, in which different plasma/particle populations and regions are strongly coupled with each other. This paper gives an overview of the ERG project and presents the initial results from the ERG (Arase) satellite.